Needs Analysis of English Language Teaching and Learning in Upper Secondary Schools - Arun Meadseena; Jiraporn Chano; Bussayarat Nithideechaiwarachok (Journal of Educational Issues, 2024)
English language teaching and learning has increased in many countries where English is not the primary language due to the advantage of using and developing language proficiency. This research aimed to explore the needs of English language teaching and learning in upper secondary schools, emphasizing listening and speaking skills. The participants were 352 students from nine upper secondary schools in northeast Thailand. Survey research was employed in the study, and the data was collected through a questionnaire comprising five aspects as an instrument. Statistics were used, including mean, standard deviation, and modified priority needs index (PNImodified). The findings found that the highest ranking from the teaching and learning management aspect was that students needed learning activities to be arranged and introduced into the lesson. Then, the highest ranking of the teacher aspect showed that students needed to use strategies or activities to assist them in developing listening and speaking skills. Next, the highest ranking of the language use aspect was the need for a variety of activities to help students use vocabulary related to the lesson, followed by the highest ranking of the English listening and speaking aspect, which was the need to encourage students to practice English listening and speaking in the classroom. Finally, the highest ranking of the assessment and reflection aspect was the need for students to be given a rating for using language in the classroom. It could be explained that the results could be beneficial for teachers, course designers, and course developers to set up courses or curricula in order to meet students’ needs.